Fertility After Treatment With High Dose Melphalan in Women With Acute Myelogenous Leukemia. Issue 2 (16th September 2015) - Even‐Or, Ehud; Ben‐Haroush, Avi; Yahel, Anat; Yaniv, Isaac; Stein, Jerry
Abstract : Background: High‐dose melphalan (HDM) is an integral component of conditioning regimens for autologous and allogeneic hematopoietic stem cell transplantation for patients with malignant and non‐malignant diseases. The gonadotoxic effects of HDM are often obscured by previous or concurrent administration of alkylating agents. From April 1996 to January 2006 our acute myeloid leukemia treatment regimen included induction and consolidation therapy with cytosine arabinoside, anthracyclines and etoposide, followed by HDM and autologous stem cell infusion. We explored gonadal function in surviving female patients so treated, who represent a unique group of patients exposed to HDM as a single gonadotoxic agent. Procedure: The fertility assessment included a questionnaire, blood tests for luteinizing hormone, follicle stimulating hormone and anti mullerian hormone (AMH), and a gynecological ultrasound exam for antral follicular count (AFC). Results: Eight female survivors participated. Although fertility assessment showed considerable damage to ovarian reserve in all participants, four of the eight female survivors conceived and bore children without medical intervention. Conclusion: In this cohort, HDM treatment reduced fertility potential but did not preclude fecundity. Early referral to a fertility clinic and long term follow‐up including serial measurements of AMH levels and AFC for female patients receiving HDM are recommended. Pediatr Blood Cancer 2015. © 2015 Wiley Periodicals, Inc.